Daily living skills scale: Development and preliminary validation of a new, open-source assessment of daily living skills - Uljarević, Mirko; Spackman, Emily K.; Cai, Ru Ying; Paszek, Katherine J.; Hardan, Antonio Y.; Frazier, Thomas W. (Frontiers in Psychiatry, 2023)
Autistic individuals and individuals with a range of other neurodevelopmental conditions (NDD) often present with lower levels of daily living skills (DLS) when compared to their neurotypical peers. Importantly, lower levels of DLS have been linked to a range of negative outcomes, including lower rates of post-secondary education, lower employment rates, and higher daily support needs across autism and NDD. However, there are currently no open-source informant-reported instruments for capturing key aspects of DLS. This study describes the development, refinement, and initial psychometric evaluation of a new, relatively brief (53-item) Daily Living Skills Scale (DLSS) in a sample of 1361 children aged 2 to 17 years. Confirmatory Factor Analysis demonstrated excellent fit of that unidimensional model to the data (CFI= .953, TLI= .951, RMSEA= .073 [95% CI: .071 -.074]). The single-factor CFA model showed evidence of measurement invariance of factor loadings, thresholds, and residual variance (strict invariance) across sex, age, race, and ethnicity. Model reliability and internal consistency were excellent (ω=.98; α=.97). Conditional reliability estimates indicated very good reliability (≥.80) for the total DLSS scale from very low (θ=-4.2) to high (θ=+2.4) scores. With further replication, the DLSS has excellent potential for wide adoption across research and clinical contexts.